Low Grade Neuroendocrine Tumors of the Lung - Melosky, Barbara (Frontiers in Oncology, 2017)
The lung is the second most common site of neuroendocrine tumours (NETs). Typical and atypical carcinoid are low grade neuroendocrine tumors of the lung. They present a favorable prognosis comported to the more common high grade neuroendocrine tumors. The low and high grade NETS require different treatment strategies; effective management of these tumours is essential to prolong survival and to manage the symptoms in patients with secretory or functional tumours. These rare tumours have received little attention and education is needed for treating physicians. This mini-review will concentrate mainly on advanced low-grade lung NETs. The article describes the classification of lung NETs and the diagnostic work-up. Different treatment methods including somatostatin analogues, peptide receptor radioligand therapy and biologic systemic therapy are discussed. Promising results from recent trials are presented and discussed in the context of the lung primary site.